Optimized Rectangular Electrode of Electrostatic Sensor - Rahmat, Mohd Fuaad (International Journal of Integrated Engineering, 2018)
This paper focuses on optimization of rectangular electrodes of electrostatic sensors. Fundamental characteristics of these electrodes are significant in order to use them in many industries that deal with particles and powders. In this study, Multi- Objective Particle Swarm Optimization (MOPSO) technique has been employed to obtain optimal value of electrode designs including length and thickness. Commercial MATLAB software is used in the optimization. Special sensitivity and statistical error have been utilized as conflict objective functions to recognize optimal sizes of electrodes. The optimization results are compared with the experimental data available in current study. From the observed results, the optimum sizes of length and thickness of rectangular electrode was equal to 0.6 cm and 0.5 cm, respectively.